Language choices during transactional Encounters at a photo shop - Ting , Su Hie; Lau, Kimberley Yih-Long (2010)
This study investigated language use between shop attendants and customers at a photo shop. The objectives were to identify languages commonly used for interaction in a smaller provision shop and to examine the responses to the uncommon language choice including how inappropriate language choices are repaired. The case study was carried out at a photo shop in Sibu. The techniques used for data collection were participant observation, video recording and semistructured interview. The participants involved were the shop attendants and customers. A total of 150 transactions were recorded. The results showed that Bahasa Melayu, Bazaar Malay Foochow, Mandarin, Hokkien and English were the common languages used in the transactions. The two instances of inappropriate language choices by the shop attendants were due to a misjudgment of the customers' ethnicity. The responses were non-verbal expressions followed by utterances in a language of wider communication. The, findings have implications on cross-cultural' communication and English for Specific Purposes courses and are applicable to the transactions in the Asian context.